2020
DOI: 10.1101/2020.03.09.984435
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From taxonomic to functional dark diversity: exploring the causes of potential biodiversity and its implications for conservation

Abstract: Aims and context: Dark diversity is an emerging and promising concept proposed to estimate the recruitment potential of natural communities and guide conservation and restoration policies. It represents all the species that could be present in a community due to favourable environmental conditions, but are currently lacking. To date, experimental approaches only measured taxonomic dark diversity, mainly based on species coexistence, which relies partly on neutral processes. Thus, these approaches may fail to i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In that way, the functional structure of local communities can be viewed as a n -dimensional functional space where species occupy different portions of this space depending on what their traits are [42,43]. Although the notion of functional observed diversity and space is well established in ecology, only recently studies started moving from theoretical exercises [4446] to empirically test the idea of ‘functional dark diversity’ [47,48]. Similar to the taxonomic species pool, we propose that the functional space of the local pool can be viewed as the functional space occupied by species present in the local community (functional observed space), and the portion of functional space that could be theoretically locally occupied but is absent (functional dark diversity) (figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In that way, the functional structure of local communities can be viewed as a n -dimensional functional space where species occupy different portions of this space depending on what their traits are [42,43]. Although the notion of functional observed diversity and space is well established in ecology, only recently studies started moving from theoretical exercises [4446] to empirically test the idea of ‘functional dark diversity’ [47,48]. Similar to the taxonomic species pool, we propose that the functional space of the local pool can be viewed as the functional space occupied by species present in the local community (functional observed space), and the portion of functional space that could be theoretically locally occupied but is absent (functional dark diversity) (figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…This approach ignores the dark diversity; the species that could thrive in a site but is absent currently, and consequently it also fails to convey information on why these species are missing. Some natural areas may harbor a relatively high diversity and yet at the same time have a high dark diversity (see for example Morel et al, 2022), but such knowledge is not revealed in studies focusing only on present diversity. This also makes traditional observed-diversity studies unsuitable for cross-habitat comparisons of the biodiversity as different habitats have different species pools (Zobel 2016).…”
Section: Introductionmentioning
confidence: 99%